The rise of the Midwestern meat packing industry - Walsh, Margaret, 1942- (The University Press of Kentucky, 2015)
The history of the meat packing industry of the Midwest offers an excellent illustration of the growth and development of the economy of that major industrial region. In the course of one generation, meat packing matured from a small-scale, part-time activity to a specialized manufacturing operation. Margaret Walsh's pioneering study traces the course of that development, shedding light on an unexamined aspect of America's economic history. As the Midwest emerged from the frontier period during the 1840s and 1850s, the growing urban demand for meat products led to the development of a seasonal.